Deciphering the Impact of miR-92a-3p on Controlling BCL11A Gene Expression and Its Implication in Easing Thalassemia Symptoms - Mohammed M. Salih Al-Khafaji; Anas Y. Al-Hayawi (Medical Journal of Babylon)
Background: Thalassemia, a prevalent genetic disorder, is characterized by a point mutation affecting the globin gene expression. One manifestation of this disorder, β-thalassemia, arises from compromised β-globin chain production. Objectives: The objective of this research was to explore the presence of miR-92a expression in the bloodstream of individuals affected by severe thalassemia. Moreover, the study aimed to uncover the functional role of miR-92a and its influence on the expression of γ-globin (HGB gene) and oxidative stress within blood cells. Materials and Methods: As an initial step, the real-time quantitative polymerase chain reaction (RT-qPCR) was employed to assess gene expression levels subsequent to RNA extraction. The process involved the addition of the polyadenosine monophosphate enzyme Poly-A to facilitate the production of mature messenger RNA (mRNA) from DNA. Results: The study revealed significantly elevated miR-92a expression in blood cells. Furthermore, higher levels of gamma-globin, glutathione (GSH), and superoxide dismutase (SOD), along with a decrease in malondialdehyde (MDA) and BCL11A expression, were identified as targets of miR-92a-3p and were downregulated by this microRNA. Additionally, individual knockdown of BCL11A led to increased expression of β-globin (HBB gene), SOD, and GSH, accompanied by a reduction in MDA levels. However, the patterns observed were altered upon subsequent inhibition of miR-92a. Conclusion: The findings of this study propose that through the suppression of BCL11A, miR-92a may elevate γ-globin levels while concurrently mitigating oxidative stress in blood cells.